Resolution of non-double-couple components in the seismic moment tensor using regional networks-I: a synthetic case study - Stierle, Eva; Vavryčuk, Vaclav; Šílený, Jan; Bohnhoff, Marco (Geophysical journal international, 2014)
We perform a detailed synthetic study on the resolution of non-double-couple (non-DC) components in the seismic moment tensors from short-period data observed at regional networks designed typically for monitoring aftershock sequences of large earthquakes. In addition, we test two different inversion approaches-a linear full moment tensor inversion and a non-linear moment tensor inversion constrained to a shear-tensile source model. The inversions are applied to synthetic first-motion P- and S-wave amplitudes, which mimic seismic observations of aftershocks of the 1999 M w = 7.4 Izmit earthquake in northwestern Turkey adopting a shear-tensile source model. To analyse the resolution capability for the obtained non-DC components inverted, we contaminate synthetic amplitudes with random noise and incorporate realistic uncertainties in the velocity model as well as in the hypocentre locations. We find that the constrained moment tensor inversion yields significantly smaller errors in the non-DC components than the full moment tensor inversion. In particular, the errors in the compensated linear vector dipole (CLVD) component are reduced if the constrained inversion is applied. Furthermore, we show that including the S-wave amplitudes in addition to P-wave amplitudes into the inversion helps to obtain reliable non-DC components. For the studied station configurations, the resolution remains limited due to the lack of stations with epicentral distances less than 15 km. Assuming realistic noise in waveform data and uncertainties in the velocity model, the errors in the non-DC components are as high as ±15 per cent for the isotropic and CLVD components, respectively, thus being non-negligible in most applications. However, the orientation of P- and T-axes is well determined even when errors in the modelling procedure are high.